Strategi Efektif dalam Menyusun Karya Ilmiah: Pelatihan Terpadu Bagi Mahasiswa - Aufa, Nauwal; Maknuni, Jauharil (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
Preparing scientific work is an essential competency that students must master in order to improve academic quality and professionalism. This research aims to identify effective strategies in compiling scientific work through an integrated training program. The research method used a descriptive approach involving 20 students from various study programs who took part in training for four weeks. This program includes technical guidance regarding topic selection, drafting an outline, mastering writing techniques, and using digital reference tools. The research results show that integrated training significantly improves students' ability to compose scientific papers. The main factors that influence success are systematic training modules, intensive mentoring, and direct simulations in preparing work. Based on these findings, integrated training is recommended as an effective strategy to improve students' ability to write quality scientific papers.